Membangun Karakter Kepedulian Lingkungan Pada Anak-Anak Di Korong Lapau Jambu Melalui Kegiatan Merawat Kebun - Ronaldo, Ronaldo; Wandi, Joni Indra; Vatin, Nurva Dillatul; Amalia, Ihsanil; Fadhila, Irwan; Mawan, Sari; Saputra, Dedy; Miftahulrahmah, Miftahulrahmah (Institut Agama Islam Sumatera Barat, 2024)
Children are a crucial age group in character formation, and it is important to equip them with positive character traits that will influence their behavior in the future. This research aims to examine the impact of character development that emphasizes environmental preservation through gardening practices in Korong Lapau Jambu. The main focus of this research is to assess the effectiveness of this activity in shaping children's personalities, particularly in relation to their perceptions of the environment. This activity involves garden maintenance with a participatory approach, where observations are made to monitor children's participation and the impact of the activities on their environmental awareness. The research results are expected to provide insights into the importance of character education based on the environment for children.